Effect of chiropractic therapy on the recovery of gastrointestinal function after gynecological abdominal surgery (捏脊疗法促进妇科腹部术后胃肠功能恢复效果观察) - SONG Limei (宋利梅); YANG Dongying (杨冬颖); GUO Miao (郭淼); WANG Zheng (王铮) (中西医结合护理)
Objective To investigate the effect of chiropractic therapy on the recovery of gastrointestinal function after gynecological abdominal surgery. Methods Totally 60 patients who meet the inclusion criteria were randomly divided into control group and study group, with 30 cases in each group. The control group was given routine nursing, while the Study group received chiropractic therapy on the basis of routine nursing. The postoperative time to first anal exhaust, time to first defecation and length of hospital stay were compared between two groups. Results There was no significant difference in time to first defecation between two groups (P＞0. 05). The postoperative time to first anal exhaust in the study group was shorter than that in the control group (P＜0. 05)). There was a significant difference in length of stay between two groups(P＜0. 05). Conclusion The chiropractic therapy is effective to improve the recovery of gastrointestinal function after gynecological abdominal surgery (目的 探讨捏脊疗法促进妇科腹部手术患者术后胃肠功能恢复的效果。方法 将符合诊断标准的60例患者随机分为对照组和研究组, 各30例。对照组给予常规护理, 研究组在常规护理的基础上实施捏脊疗法。对比两组术后首次排气、排便时间、住院时间。结果 两组患者术后首次排便时间比较, 差异无统计学意义(P＞0. 05)。研究组术后首次排气较对照组缩短, 差异有统计学意义(P＜0. 05)。两组住院时间比较, 有统计学意义(P＜0. 05)。结论 捏脊疗法能够促进妇科腹部术后胃肠功能恢复。)